The Washington MS. of the Gospels - Streeter, B. H. (Harvard theological review, 1926)
One of the great glories of the Freer Gallery of the Smithsonian Institution at Washington is the MS. of the Four Gospels, commonly cited as W, which was bought in Egypt in 1906, and may have been found in the ruins of an Egyptian monastery. With regard to it Professor A. S. Hunt, after again looking at photographs of the MS., writes me: “A date within the fourth century seems to me quite possible, but the early fifth century is not to be excluded. Personally I should incline to put it towards the end of the fourth century…. But… the first quire of John is obviously considerably later.” Thus W is probably the third oldest MS. of the gospels in Greek. Yet on account of the extraordinary variety in the types of early text contained in it, W is of all MSS. the most enigmatic. I hope in this article to contribute something towards the solution of the enigma.